Is There a Rationale to Contact the Unemployed Right from the Start? Evidence from a Natural Field Experiment - Bert van Landeghem; Frank Cörvers; Andries de Grip (Institute for the Study of Labor (IZA), 2016)
Active Labour Market Policies often exclusively target towards the long-term unemployed. Although it might be more efficient to intervene earlier in order to prevent long-term unemployment rather than to cure it, the climate of austerity in Eurozone countries is spreading a tendency to further reduce the basic counselling for those who become unemployed. This study investigates the impact on employment chances of a relatively light and inexpensive programme that is offered right after the start of the unemployment spell. It comprises of a collective information session followed by a short one-on-one interview. In a field experiment carried out with an employment office in Flanders, a random selection of clients (the treatment group) were invited to the programme within one month after being enrolled as unemployed, while the control group were scheduled to have the information session five months after becoming unemployed. We find a substantial intention- to-treat effect in the first four months after the start of the unemployment spell, and the early intervention seems especially beneficial for those with low education.
Keywords: D04; D61; J64; J68; 330; Active Labour Market Policies; unemployment; nudging; natural field